Association Between Fibroblast Growth Factor Receptor 1 Gene Amplification and Human Papillomavirus Prevalence in Tonsillar Squamous Cell Carcinoma With Clinicopathologic Analysis. (July 2018) - Park, Soonchan; Lee, Miji; Cho, Kyung-Ja; Kim, Sung Bae; Roh, Jong-Lyel; Choi, Seung-Ho; Nam, Soon Yuhl; Kim, Sang Yoon; Song, Joon Seon
Amplification of fibroblast growth factor receptor 1 ( FGFR1 ) has been reported in many squamous cell carcinomas, and human papillomavirus (HPV)–related oropharyngeal squamous cell carcinoma has been characterized as a distinct subset with favorable prognosis. Here, we investigated the FGFR1 amplification and HPV status in tonsillar squamous cell carcinoma (TSCC) and analyzed the clinical characteristics. HPV in situ hybridization (HPV ISH) and FGFR1 fluorescence in situ hybridization (FISH) were performed using tissue microarray from 89 cases of TSCC. Fourteen of 89 (15.7%) TSCC cases had FGFR1 amplification, and HPV was detected in 59 of 89 (66.3%) cases. FGFR1 amplification status was not associated with HPV positivity ( p =0.765). Outcomes were not significantly different between FGFR1 amplified and non-amplified patients. Although FGFR1 amplified patients ( n =4) in the HPV ISH–negative group ( n =30) had a tendency for poorer overall survival, no statistical significance was identified ( p =0.150, log-rank). FGFR1 protein overexpression showed better disease-free survival ( p =0.031, log-rank) in HPV-negative TSCC. This study suggests FGFR1 amplification may be important in the pathogenesis of TSCC regardless of HPV status.